1983
DOI: 10.1002/bjs.1800701209
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported dark red bleeding as a marker comparable with occult blood testing in screening for large bowel neoplasms

Abstract: The study was designed to determine the prevalence of large bowel symptoms in an adult working population and to assess their value in screening for large bowel neoplasms. A symptom questionnaire was sent to workers in two large organizations and the results were compared with faecal occult blood testing in the same individuals using Haemoccult (Eaton Laboratories). Completed symptom questionnaires and Haemoccult test kits were returned by 916 out of a total of 1805 employees over the age of 40 (compliance 50.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

1985
1985
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 12 publications
0
15
0
5
Order By: Relevance
“…Dark red bleeding is commonly thought to be a useful discriminating factor, but its high incidence in patients with benign disease shown in this study decreases its value and previous studies on this have been contradictory [ 15–17].…”
Section: Discussionmentioning
confidence: 56%
“…Dark red bleeding is commonly thought to be a useful discriminating factor, but its high incidence in patients with benign disease shown in this study decreases its value and previous studies on this have been contradictory [ 15–17].…”
Section: Discussionmentioning
confidence: 56%
“…In one previous study workers over 40 years of age in two companies were invited to receive a Haemoccult kit and complete a symptom questionnaire. 22 Although overall compliance was 51% with women participating significantly more than men (61% v 47%), uptake according to age and occupation were not reported. The intense publicity with lectures, leaflets, and small group discussion may have encouraged greater participation than in our study.…”
Section: Discussionmentioning
confidence: 93%
“…In Portsmouth, UK, a prevalence of 18% was noted for rectal bleeding in the previous year in individuals over 16 years [24]. All these studies also demonstrated a higher prevalence of rectal bleeding in younger age groups [16,[20][21][22][23][24][25][26].…”
Section: Prevalencementioning
confidence: 99%